Modular Microphysiological System for Modeling of Biologic Barrier Function - Ishahak, Matthew; Hill, Jordan; Amin, Quratulain; Wubker, Laura; Hernandez, Adiel; Mitrofanova, Alla; Sloan, Alexis; Fornoni, Alessia; Agarwal, Ashutosh (Frontiers in Bioengineering and Biotechnology, 2020)
Microphysiological systems, also known as organs-on-chips, are microfluidic devices designed to model human physiology in vitro. Polydimethylsiloxane (PDMS) is the most widely used material for organs-on-chips due to established microfabrication methods, and properties that make it suitable for biological applications such as low cytotoxicity, optical transparency, gas permeability. However, adsorption of hydrophobic compounds and leaching of uncrosslinked oligomers might hinder the adoption of PDMS-based organs-on-chips for drug discovery assays. Here, we have engineered a modular, PDMS-free microphysiological system that is capable of recapitulating biologic barrier functions commonly demonstrated in PDMS-based devices. Our microphysiological system is comprised of a microfluidic chip to house cell cultures and pneumatic microfluidic pumps to drive flow with programmable pressure and shear stress. The modular architecture and programmable pumps enabled us to model multiple in vivo microenvironments. First, we demonstrate the ability to generate cyclic strain on the culture membrane and establish a model of the alveolar air-liquid interface. Next, we utilized three-dimensional finite element analysis modeling to characterize the fluid dynamics within the device and develop a model of the pressure-driven filtration that occurs at the glomerular filtration barrier. Finally, we demonstrate that our model can be used to recapitulate sphingolipid induced kidney injury. Together, our results demonstrate that a multifunctional and modular microphysiological system can be deployed without the use of PDMS. Further, the bio-inert plastic used in our microfluidic device is amenable to various established, high-throughput manufacturing techniques, such as injection molding. As a result, the development plastic organs-on-chips provides an avenue to meet the increasing demand for organ-on-chip technology.